Willing and able? a primer on the international criminal court's jurisdiction over the Philippine war on drugs - Batuhan, Juan Emmanuel P. (Philippine Law Journal, 2019)
The question that this Article will answer is whether the waging of the Philippine War on Drugs constitutes a case that can be tried by the International Criminal Court (ICC). This demands an examination of both the Court's jurisdiction and the case's admissibility, since having jurisdiction does not automatically entitle the ICC to exercise it-the case must also be admissible. In this Article, the authors will demonstrate the application of the Rome Statute as legal basis for the conclusion that the ICC has jurisdiction over the acts perpetrated before the Philippines' withdrawal, and that the Philippines' case is admissible, despite the government's invocation of complementarity. The Rome Statute is the primary point of reference with regard to discussion of the Court and its jurisdiction, as it is the treaty that established the ICC which sits as the first permanent international criminal court.